The impact of entrepreneurial awareness on small and medium enterprises in the light of the requirements of the national transformation program - Alhathli, Najwa Samran Awad (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to measure the impact of entrepreneurial awareness on SMEs in light of the requirements of the national transformation program, , In this study, the researcher relied on the descriptive survey method in order to obtain facts and information related to the problem of the study by dividing and analyzing this data for the purposes of the study, The questionnaire was used as a data collection tool, which consisted of four axes, The importance of the study explain the role of the National Transformation Program in entrepreneurship, raising awareness and knowledge of the owners of these projects, and measuring its impact on small and medium enterprises, The study population consisted of all owners of small and medium enterprises in the Kingdom of Saudi Arabia, and an intentional random sample was taken from the owners of small and medium enterprises in the Makkah region, Among the most important findings of the study is the high level of entrepreneurial awareness in small and medium enterprises, and the initiatives contributed to increasing the contribution of small and medium enterprises to the local economy through the necessity of entrepreneurship in light of the developments taking place in the world, and one of the most prominent recommendations was to define a strategy for SMEs that reflects the implementation plan by the Ministries of Planning and Social Affairs in accordance with objectives and ambitions.
Keywords: entrepreneurial awareness; small and medium enterprises; national transformation program